Flint 'figurines' from the Early Neolithic site of Kharaysin, Jordan. (August 2020) - Ibáñez, Juan José; Muñiz, Juan R.; Huet, Thomas; Santana, Jonathan; Teira, Luis C.; Borrell, Ferran; Rosillo, Rafael; Iriarte, Eneko
Abstract: Abstract : During the Early Neolithic in the Near East, particularly from the mid ninth millennium cal BC onwards, human iconography became more widespread. Explanations for this development, however, remain elusive. This article presents a unique assemblage of flint artefacts from the Middle Pre-Pottery Neolithic B (eighth millennium BC) site of Kharaysin in Jordan. Contextual, morphological, statistical and use-wear analyses of these artefacts suggest that they are not tools but rather human figurines. Their close association with burial contexts suggests that they were manufactured and discarded during mortuary rituals and remembrance ceremonies that included the extraction, manipulation and redeposition of human remains.